Pengaruh Pupuk NPK Tunggal, Majemuk, dan Pupuk Daun terhadap Peningkatan Produksi Padi Gogo Varietas Situ Patenggang - PUTRA, SUNJAYA (Agrotrop : Journal on Agriculture Science; Vol 2 No 1 (2012), 2013)
Increasing rice yield for fulfill food can be done through utilization dryland for planted new varieties upland rice and granting fertilizer appropriate. The study aims to determine the effect of NPK singular, compound and fertilizers leaf to increased upland rice yield of Situ Patenggang varieties. The experiment was conducted at dryland in Nagrak Utara village, Sukabumi District in West Java on January to April 2008. Materials research are used upland rice Situ Patenggang varieties, NPK Phonska (15-15-15), Urea, SP 36, KCl and fertilizers leaf. The experiment uses Randomized Block Design of six treatments and four replications. Treatments consisted of; 1) NPK 250 kgha-1, 2) NPK 200 kgha-1+ Urea 100 kgha-1, 3) NPK 200 kgha-1 + Urea 50 kgha-1+ Fertilisers leaf 3 lha-1, 4) NPK 200 kgha-1+ Urea 100 kgha-1+ Fertilisers leaf 2 lha-1, 5) NPK 200 kgha-1+ Fertilisers leaf 3 lha-1, 6) Urea 200 kgha-1+ SP 36 100 kgha-1+ KCl 50th kgha-1. The resulth of experience conclused that fertilizing treatment with NPK 200 kgha-1+ Urea 50 kgha-1+ Fertilisers leaf 2 lha-1 represents dosing appropriate and can increase upland rice yield of Situ Patenggang varieties until 3.4 tonsha-1 or increased counted 58% compared treatment using single fertilizers only (Urea 200 kgha-1+ SP 36 100 kgha-1+ KCl 50 kgha-1).
Keywords: fertilizer, upland rice, yield